2020
DOI: 10.3390/nano10122439
|View full text |Cite
|
Sign up to set email alerts
|

The Antifungal Mechanism of Amphotericin B Elucidated in Ergosterol and Cholesterol-Containing Membranes Using Neutron Reflectometry

Abstract: We have characterized and compared the structures of ergosterol- and cholesterol-containing 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) membranes before and after interaction with the amphiphilic antifungal drug amphotericin B (AmB) using neutron reflection. AmB inserts into both pure POPC and sterol-containing membranes in the lipid chain region and does not significantly perturb the structure of pure POPC membranes. By selective per-deuteration of the lipids/sterols, we show that AmB extracts erg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…39 However, its water-soluble oligomers are highly toxic due to their relatively high affinity to the cholesterol in the host cell, while the monomeric form binds explicitly to ergosterol, reducing the host cell toxicity. 40 Achieving the monomerization of AmB generally relies on employing biocompatible lipid carriers, which induce disaggregation with longer chain surfactants. Additionally, previous reports revealed the more effective monomerization of AmB by micellar stearates, as present in the VBS coated on SLNs, for improving the lipid compatibility of the hydrophilic VB 12 .…”
Section: Resultsmentioning
confidence: 99%
“…39 However, its water-soluble oligomers are highly toxic due to their relatively high affinity to the cholesterol in the host cell, while the monomeric form binds explicitly to ergosterol, reducing the host cell toxicity. 40 Achieving the monomerization of AmB generally relies on employing biocompatible lipid carriers, which induce disaggregation with longer chain surfactants. Additionally, previous reports revealed the more effective monomerization of AmB by micellar stearates, as present in the VBS coated on SLNs, for improving the lipid compatibility of the hydrophilic VB 12 .…”
Section: Resultsmentioning
confidence: 99%
“…For ergosterol, the principal native fungal sterol, production of a deuterated material in Pichia and its use in neutron studies have been reported, including a methodology for the isolation of the material in high purity by precipitation. 25,26…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Kaminski made an argument that the fungal cell wall is made up of hydrophilic chitin, which poses a serious obstacle in transporting ergosterol from the cell membrane and into the polyene aggregates. Additionally, there is evidence that not only is the affinity lower for cholesterol, but that AmB does not extract it from POPC membranes [ 163 ]. The authors used neutron reflectometry and found that AmB is not capable of extracting cholesterol from a POPC-cholesterol lipid bilayer, but it does extract ergosterol from a POPC-ergosterol lipid bilayer.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%